Simplified Printed Log-Periodic Dipole Array Antenna Fed by CBCPW - Guohua Zhai; Yong Cheng; Qiuyan Yin; Shouzheng Zhu; Jianjun Gao (International Journal of Antennas and Propagation, 2013)
A novel simple approach for designing single-layer printed log-periodic dipole array (PLPDA) antenna fed by conductor-backed coplanar waveguide (CBCPW) is presented. The PLPDA antenna has the merits of wide bandwidth, low profile, and stable radiation pattern, which should be fed by the balanced line. The balanced line, created by the geometric features of the CBCPW, provides a balun with a considerably wide bandwidth with low profile, broad bandwidth, low insertion loss, and so forth. The prototype of the proposed CBCPW-fed printed log-periodic array at Ka band is designed and fabricated; the measured data are in good agreement with the simulated results.